WHOLESOME SCATTERING GAME AS A TECHNIQUE TO IMPROVE STUDENTS’ WRITING ON DESCRIPTIVE TEXT AT SMP NEGERI 3 PEMATANG SIANTAR - Natanael Saragih (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2020)
The aim of this research is to find out the implementation of Wholesome Scattering Game in improving the students’ ability in writing descriptive text. The population of this research was all of the eighth grade students of SMP N 3 Pematangsiantar, which consisted 312 students as the population and 31 as the sample. This research was conducted by Classroom Action Research with two cycles. The finding of this research is the researcher got good result from activities of teaching descriptive text using Wholesome Scattering Game technique. The quantitative data was taken from the tests, which were pre-test and post-test in first cycle and post-test II in second cycle. The improvement is the mean of the pre-test is 57,61 in first cycle. But it increase to be 74,19 in the post-test. And researcher found that the mean score of students increased up to be 80.67 in post-test II in second cycle. Difference calculation of the mean in cycle I is 16.58; and the standard deviation is 5.2. Beside that the standard error for the mean difference is 0.95. And researcher found that the t-test of this research was 17.45, with the effect size of the test was 3.18. From the explanation previous shows that by applying Wholesome Scattering Game technique can improve their writing ability. The difference calculation in the second cycle (post-test I and post-test II), the mean was 6.48, and standard deviation was 2.33. Besides that, the standard error for the mean difference was 0.42, and t-test was 15.42. To improve that the Wholesome Scattering Game was very significant to improve students’ writing skills especially in descriptive text, researcher give the result of the effect size, namely was 2.78. Based on the explanation above, the researcher concludes that wholesome scattering game is effective to be used in teaching writing descriptive text which could interesting and useful to increase students' writing ability and students will not bored and passive in the class because they learn while interact with wholesome scattering game